1993
DOI: 10.1007/bf00036098
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylation of cyclodextrin-complexed podophyllotoxin by cell cultures of Linum flavum L.

Abstract: The glucosylation of the cytotoxic lignan podophyllotoxin by cell cultures derived from Linum flavum was investigated. Four cyclodextrins: /3-cyclodextrin, y-cyclodextrin, dimethyl-/3-cyclodextrin and hydroxypropyl-/3-cyclodextrin were used to improve the solubility of podophyllotoxin by complexation. Dimethyl-/3-cyclodextrin met our needs the best and the solubility of podophyllotoxin could be enhanced from 0.15 to 1.92 mM, using a podophyllotoxin/cyclodextrin ratio of 1 : 1. Growth parameters of the cell sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Feeding experiments with cell cultures of Podophyllum hexandrum (accumulating podophyllotoxin as the main lignan) and L.¯avum with 6-methoxypodophyllotoxin as the main lignan showed that P. hexandrum converted deoxypodophyllotoxin into podophyllotoxin whereas L.¯avum accumulated 6-methoxypodophyllotoxinb-D-glucoside after feeding of deoxypodophyllotoxin (Van Uden et al 1995, 1997a. Cell cultures of L.¯avum converted exogenously applied podophyllotoxin to podophyllotoxin-b-D-glucoside and not to 6-methoxypodophyllotoxin (Van Uden et al 1993, 1997a. Feeding of b-peltatin resulted in the formation of 6-methoxypodophyllotoxin-b-D-glucoside and b-peltatin-b-D-glucoside in L.¯avum.…”
Section: Discussionmentioning
confidence: 96%
“…Feeding experiments with cell cultures of Podophyllum hexandrum (accumulating podophyllotoxin as the main lignan) and L.¯avum with 6-methoxypodophyllotoxin as the main lignan showed that P. hexandrum converted deoxypodophyllotoxin into podophyllotoxin whereas L.¯avum accumulated 6-methoxypodophyllotoxinb-D-glucoside after feeding of deoxypodophyllotoxin (Van Uden et al 1995, 1997a. Cell cultures of L.¯avum converted exogenously applied podophyllotoxin to podophyllotoxin-b-D-glucoside and not to 6-methoxypodophyllotoxin (Van Uden et al 1993, 1997a. Feeding of b-peltatin resulted in the formation of 6-methoxypodophyllotoxin-b-D-glucoside and b-peltatin-b-D-glucoside in L.¯avum.…”
Section: Discussionmentioning
confidence: 96%
“…The complexation of desoxypodophyllotoxin with dimethyl-/~-cyclodextrin at a ratio 1:1 and at a concentration of 2 mM was rapid and complete, after 3 h. It has been reported previously that cyclodextrins applied at a concentration of 2 mM did not affect the growth characteristics of cell suspensions of Podophyllurn hexandrum (Woerdenbag et al 1990b) and of Linumflavum (Van Uden et al 1993). Also in this study the use of dimethyl-/~-cyclodextrin at a final concentration of 1.4 mM did not affect the growth characteristics.…”
Section: Cyclodextrin-complexed Desoxypodophyllotoxin As a Substratementioning
confidence: 88%
“…To enable feeding of the very apolar desoxypodophyllotoxin to plant cell cultures in a dissolved state, the substrate was first complexed with dimethyl-~-cyclodextrin (Van Uden et al 1993). The complexation of desoxypodophyllotoxin with dimethyl-/~-cyclodextrin at a ratio 1:1 and at a concentration of 2 mM was rapid and complete, after 3 h. It has been reported previously that cyclodextrins applied at a concentration of 2 mM did not affect the growth characteristics of cell suspensions of Podophyllurn hexandrum (Woerdenbag et al 1990b) and of Linumflavum (Van Uden et al 1993).…”
Section: Cyclodextrin-complexed Desoxypodophyllotoxin As a Substratementioning
confidence: 99%
See 2 more Smart Citations